1998
DOI: 10.1074/jbc.273.4.2260
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosylation and Structure of Human Serum IgA1, Fab, and Fc Regions and the Role of N-Glycosylation on Fcα Receptor Interactions

Abstract: The human serum immunoglobulins IgG and IgA1 are produced in bone marrow and both interact with specific cellular receptors that mediate biological events. In contrast to IgA1, the glycosylation of IgG has been well characterized, and its interaction with various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
366
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(394 citation statements)
references
References 80 publications
23
366
5
Order By: Relevance
“…Indeed, only 6-19 IgA RF was highly O-glycosylated in its hinge region, consistent with finding that the occupancy of the O-linked glycosylation site is partial in human IgA1. 10,11 The attachment of GalNAc to serine or threonine is catalyzed by UDP-N-acetylgalactosaminyl transferases (GalNAcT); a study in human B cells reported that among the six GalNAcTs expressed in these cells, GalNAcT2 exhibited the highest catalytic activity in transferring GalNAc to a synthetic peptide corresponding to the hinge region of human IgA1. 26 In agreement with this finding, our ongoing analysis showed approximately eightfold higher levels of GalNAcT2 mRNA in 6-19 transfectomas than in 46-42 hybridoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, only 6-19 IgA RF was highly O-glycosylated in its hinge region, consistent with finding that the occupancy of the O-linked glycosylation site is partial in human IgA1. 10,11 The attachment of GalNAc to serine or threonine is catalyzed by UDP-N-acetylgalactosaminyl transferases (GalNAcT); a study in human B cells reported that among the six GalNAcTs expressed in these cells, GalNAcT2 exhibited the highest catalytic activity in transferring GalNAc to a synthetic peptide corresponding to the hinge region of human IgA1. 26 In agreement with this finding, our ongoing analysis showed approximately eightfold higher levels of GalNAcT2 mRNA in 6-19 transfectomas than in 46-42 hybridoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide fraction containing the 62-amino acid hinge peptide of each IgA mAb obtained by treatment with trypsin and lysylendopeptidase ( Figure 4) was collected by HPLC and subjected to matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS). The analysis of [6][7][8][9][10][11][12][13][14][15][16][17][18][19] IgA RF mAb identified, in addition to a peak containing the nonglycosylated hinge peptide at m/z 6627, four additional peaks of O-glycosylated hinge peptides, which contained GalNAc monosaccharide, GalNAc-Gal disaccharide, and its monoand disialylated forms ( Figure 5). The prevailing form of the carbohydrate composition of O-glycans was GalNAc-Gal disaccharide at m/z 6992, and the abundance of the glycosylated peptide ions at this peak was similar to that of the nonglycosylated ones.…”
Section: Similar Proportion Of Polymeric and Monomericmentioning
confidence: 99%
See 1 more Smart Citation
“…ASGP-R and FcaRI involved in the degradation of desialylated IgA.The IgA is glycoprotein and it has potential glycosylation sites within hinge region [37]. It has been reported that with these glycosylated residues (Asn263 and Asn459) IgA binds to ASGPR and ASGPR done its degradation [39].…”
Section: Immunoglobulin a Receptormentioning
confidence: 99%
“…However, human IgA1 also contains variable O-glycan side chains within the hinge region, which could cause variation in the size of the heavy chain fragments due to deglycosylation. 31 In order to eliminate this possibility, the IgA1 protease (NTHI 6988 ) was also incubated with deglycosylated human IgA1. This still resulted in two Fc fragments, which did not degrade further.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%